Obnova vozišč z BSM-tehnologijo - Zore, Damjan (Gradbeni vestnik, 2023)
As part of the renovation of existing roadways, renovations are also carried out by stabilizing existing pavements using cold process with bitumen. Stabilization with foamed bitumen has been present in Slovenia since 2000. In 2021, we at Igmat, d. d., prepared the Technical specification for transport infrastructure (TSPI-PGV.06.325:2022) RS MZI, 2022 for BSM (bitumen stabilised materials). The specification addresses a wider range of binder applications than those currently in use, gives the parameters for determining the suitability of road sections for this type of rehabilitation and the selection of the most appropriate stabilization technology. It describes the novelties in design, execution of work, quality control and states the requirements for the quality characteristics of the materials used, the produced mixture, the embedded layer and the frequency of testing.
Keywords: BSM technology; BSM-tehnologija; financial and environmental benefits; finančne in okoljske koristi; foamed bitumen; penjeni bitumen